Development of Experimental Setup to Investigate the Control System for Infusion Solutions Dosing Process - Fedir Matiko; Volodymyr Shaleva (Energy Engineering and Control Systems, 2024)
The paper presents the results on developing an experimental setup for the research into the control system for the solution dosing process based on the weighing method of dosing. According to the results of the dosing process analysis, in the dosing systems of materials or solutions, the critical parameter is the speed of the controller and the time of its communication with peripheral devices. At the same time, it is necessary to ensure the possibility of implementing the necessary control algorithms, as well as supervision of the process. Taking into account these criteria, the authors selected a programmable logic controller (PLC) and developed a pilot plant for the study of the solution dosing process control system. The experimental setup makes it possible to study various control system structures and their dynamic characteristics depending on the characteristics of the programmable logic controller and weighing modules. According to the analysis of the technical characteristics of controllers from well-known manufacturers Siemens, Rockwell Automation and Mitsubishi Electric, the Siemens CPU 1215C DC/DC/DC controller with ET-200SP remote input/output station and SIWAREX WP321 weighing module were selected for the implementation of the experimental setup. Research on the selected programmable logic controller and the dosing process control system was performed. The results of research confirmed that using CPU 1215C DC/DC/DC controller, it is possible to achieve the same speed and productivity of the dosing line as when using control systems based on single-chip processors, while significantly expanding the functional capabilities of the system. The algorithm for controlling the process of dosing the infusion solutions was also improved in order to adapt it to controlling the process of dosing the solutions of different viscosities into bottles of different capacities. The effectiveness of the control system based on the PLC, which is part of the experimental setup, was assessed, in particular, the cycle time of the developed algorithm was estimated. Based on the results of evaluating the duration of the controller program cycle, it was concluded that the use of the developed control system as part of the WDM 8002 type infusion solution dosing line will make it possible to achieve the required line productivity and integrate the control system into the process and production control levels.